2013
DOI: 10.1370/afm.1512
|View full text |Cite
|
Sign up to set email alerts
|

eCHAT for Lifestyle and Mental Health Screening in Primary Care

Abstract: PURPOSE Early detection and management of unhealthy behaviors and mental health issues in primary care has the potential to prevent or ameliorate many chronic diseases and increase patients' well-being. This study aimed to assess the feasibility and acceptability of the systematic use of a Web-based eCHAT (electronic Case-finding and Help Assessment Tool) screening patients for problematic drinking, smoking, and other drug use, gambling, exposure to abuse, anxiety, depression, anger control, and physical inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…The vast majority of patients reported that the system was easy to use (94%), and 77% of patients were willing to have GPs keep their survey responses on file [28]. Similar findings have been reported in studies from New Zealand, the United Kingdom, and the United States [29,30]. Patients report that electronic assessments are sufficiently private (91%) [30] and indicate a preference for electronic approaches over paper and pen assessments.…”
Section: Improving the Comprehensiveness And Accuracy Of Clinical Infmentioning
confidence: 59%
“…The vast majority of patients reported that the system was easy to use (94%), and 77% of patients were willing to have GPs keep their survey responses on file [28]. Similar findings have been reported in studies from New Zealand, the United Kingdom, and the United States [29,30]. Patients report that electronic assessments are sufficiently private (91%) [30] and indicate a preference for electronic approaches over paper and pen assessments.…”
Section: Improving the Comprehensiveness And Accuracy Of Clinical Infmentioning
confidence: 59%
“…Most of these studies have used small convenience samples, 24,[43][44][45] with the exceptions of eCHAT, Promote Health and My Own Health Report (MOHR). 22,46,47 Each of these studies, although valuable, either does not include a control group (eCHAT), is limited to academic settings with an above average income population (Promote Health) or is not widely available for use (MOHR). In this emerging area of patient-centred clinical informatics, the iCCAS study advances the field by recruiting an immigrant, refugee and ethnoracially diverse patient population from a community health centre and using rigorous randomized controlled design.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in New Zealand demonstrated the feasibility of an electronic lifestyle assessment tool similar to the IWT. 22 While the results of that assessment may be downloaded from a website to the electronic medical record by the provider, they do not drive automatic order prompts, thus increasing the steps required to implement a relevant care plan. Despite this difference, most patients in that study found the tool easy to use, and feedback from providers was positive.…”
Section: Discussionmentioning
confidence: 99%